Psychological factors in the irritable bowel syndrome. Issue 10 (October 1987) - Creed, F; Guthrie, E
Abstract : This paper reviews recent psychological studies of patients with the irritable bowel syndrome (IBS) or 'functional abdominal pain'. Many studies have used unreliable or invalid methods of assessment and some have confused personality with treatable psychiatric illness. Reliable and valid measures have indicated that 40-50% of patients with recently diagnosed functional abdominal pain have demonstrable psychiatric illness; these patients have a worse prognosis than those who are psychologically normal. When psychiatric disorder is diagnosed in a patient with IBS there are three possibilities: (1) The patient may have developed abdominal and psychiatric symptoms simultaneously in which case treatment of the latter may relieve the bowel symptoms. (2) Psychiatric disorder may precipitate increased concern about bowel symptoms, and consequent attendance at the gastroenterology clinic, of those with chronic mild symptoms. In this case it is illness behaviour, rather than abdominal symptoms, that is caused by the anxiety/depression. (3) Those with chronic neurotic symptoms as part of their personality must be screened for organic disease if they have a fresh onset of bowel symptoms; but they are at high risk of becoming persistent clinic attenders. Further research is needed to clarify when psychological abnormalities play a role in the aetiology of IBS and when they are coincidental, but lead to illness behaviour. The role of psychological factors in the aetiology of the irritable bowel syndrome (IBS) is far from clear, but a review of the literature suggests that some consistent patterns are emerging in spite of methodological problems. There have been three major defects with studies that have linked IBS with neurotic symptomatology. First, the measurement of psychological factors has generally been imprecise. Second, most studies have considered IBS patients as a single group, without making allowance for differing symptom patterns. Third, conclusions have been drawn about hospital samples and extrapolated to all IBS subjects, without taking account of factors which affect consulting behaviour. Most studies have been concerned with psychological factors so these will be considered in most detail.